2017
DOI: 10.36076/ppj.2017.e283
|View full text |Cite
|
Sign up to set email alerts
|

Rapid and Delayed Effects of Pulsed Radiofrequency on Neuropathic Pain: Electrophysiological, Molecular, and Behavioral Evidence Supporting Long-Term Depression

Abstract: Background: Pulsed radiofrequency (PRF) has been widely employed for ameliorating clinical neuropathic pain. How PRF alters electrophysiological transmission and modulates biomolecular functions in neural tissues has yet to be clarified. We previously demonstrated that an early application of low-voltage bipolar PRF adjacent to the dorsal root ganglion (DRG) reduced acute neuropathic pain in animals. By contrast, the present study investigated how PRF alters postsynaptic sensitization to produce early and dela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 52 publications
0
7
0
Order By: Relevance
“…reported that long-term PRF treatment in mice triggered the recovery of resinoid-induced mechanical pain by inhibiting extracellular signal-regulated kinase (ERK). Ren Yu et al [38]. observed that PRF alleviated persistent neuropathic pain by selectively inhibiting the generation of long-term depression, inhibiting the activation of ERK in neurons and astrocytes in the superficial dorsal horn, and selectively and continuously regulating C fiber-mediated spinal cord nociceptive hypersensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…reported that long-term PRF treatment in mice triggered the recovery of resinoid-induced mechanical pain by inhibiting extracellular signal-regulated kinase (ERK). Ren Yu et al [38]. observed that PRF alleviated persistent neuropathic pain by selectively inhibiting the generation of long-term depression, inhibiting the activation of ERK in neurons and astrocytes in the superficial dorsal horn, and selectively and continuously regulating C fiber-mediated spinal cord nociceptive hypersensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…[15,16,21,22] The exact analgesic mechanism of PRF remains unclear. At present, it is hypothesized that an electromagnetic field is generated around the target nerve, thus activating pain inhibitory pathways, reducing norepinephrine and 5-hydroxytryptamine, [23] inhibiting the activity of excitatory nociceptive C-fibers, [24,25] reducing the release of excitatory amino acids such as glutamate, [26] inhibiting pro-inflammatory cytokines, [27,28] activating dorsal horn pain-processing neurons, [29] and reducing microglial activation. [30] It is well known that PRF is effective in relieving peripheral NP, such as postherpetic neuralgia, carpal tunnel syndrome, occipital neuralgia, etc.…”
Section: Discussionmentioning
confidence: 99%
“…1E) for 5, 10, or 20 min in different groups based on our previous study. 25 The animals were given 1 week to recover postsurgery. Correct SCS device implantation was ensured by at least once weekly impedance tests to confirm optimal current conductivity.…”
Section: Methodsmentioning
confidence: 99%
“…4B): A-components (10 to 220 ms, including Aβ and Aδ fiber-mediated transmission) and C-components (220 to 1,010 ms, C fiber-mediated transmission). 25,[30][31][32] Under stable anesthesia, baseline local field potentials in the primary somatosensory and anterior cingulate cortices were quiescent (fig. 4A).…”
Section: Electrical Hind Paw Stimulation Evoked Local Field Potential...mentioning
confidence: 99%